Current trends in definition and treatment of Raynaud’s phenomenon - I. R. Gaisin; Z. R. Bagautdinova (Лечащий Врач)
The review is Dedicated to the analysis of modern literature on the definition, classification and diagnostics of Raynaud’s phenomenon, describes the main causes of secondary RP, clinical manifestations of RP, the importance of capillaroscopy in the early diagnostics of rheumatic diseases, principles of treatment of RP.